2015
DOI: 10.1111/tran.12083
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to religious adulthood: relational geographies of youth, religion and international volunteering

Abstract: This paper offers important insights into the contemporary nature of youth transitions and the ways in which religious affiliation and engagement with international volunteering influences and interplays with negotiations of the life course. Situated within interdisciplinary debates about youth transitions, as well as discussions about relational geographies of age, religion and voluntarism, we demonstrate the multiple relationalities that are at play as young religious international volunteers negotiate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…To better understand these processes requires becoming attuned to particular religious vocabularies, or looking where they may currently be no vocabularies to describe participatory activity which is not quite ‘secular’ or devoid of religion, but religiously/spiritually informed. As Hopkins, Olson, Baillie Smith and Laurie (: 390) have suggested, it also invites a reorientation ‘away from a focus on the individual acquisition of skills’ through a linear and cumulative perception of religious practice or activities as leading to civic capacity, and towards the ‘multiple and perhaps alternative understandings of what it means to be an adult’ for religious youth, in the context of the fragmentation of pathways towards becoming an engaged and socially responsible citizen.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand these processes requires becoming attuned to particular religious vocabularies, or looking where they may currently be no vocabularies to describe participatory activity which is not quite ‘secular’ or devoid of religion, but religiously/spiritually informed. As Hopkins, Olson, Baillie Smith and Laurie (: 390) have suggested, it also invites a reorientation ‘away from a focus on the individual acquisition of skills’ through a linear and cumulative perception of religious practice or activities as leading to civic capacity, and towards the ‘multiple and perhaps alternative understandings of what it means to be an adult’ for religious youth, in the context of the fragmentation of pathways towards becoming an engaged and socially responsible citizen.…”
Section: Resultsmentioning
confidence: 99%
“…ENDNOTES 1 RES-451-26-0561, AH/G016461/1. 2 For more details of broader research findings see Hopkins et al (2015), Baillie Smith et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research is also focusing on citizenship, with Lorimer () addressing environmental citizenship and others examining different forms of cosmopolitanism (Baillie Smith, Laurie, Hopkins, & Olson, ; Craggs, ; Rovisco, ; Snee, ) and partnership (Baillie Smith & Laurie, ; Schech, Mundkur, Skelton, & Kothari, ). In these contexts, wide‐ranging scholarship has addressed how volunteers understand their experiences as part of a faith journey (Baillie Smith et al., ; Brickell, ; Hopkins, Baillie Smith, Laurie, & Olson, ) and/or as an expression of transnational solidarity (Henderson, ). Research has also explored how volunteers' practices link to geographies of care, responsibility, “lifestyle politics” and emotion as people aim to “do good” (e.g.…”
Section: A Partial Geography Of International Volunteeringmentioning
confidence: 99%
“…A study of evangelical Christian adolescents from the United Kingdom participating in non-medical, short-term mission trips to Central and South America found that participants developed an increase in their ability to share their faith with others and a stronger sense of being close to God (Hopkins et al 2015). A different study of North American youth who participated in short-term mission trips found that they were also more likely to become civically engaged in volunteer work and political activity (Beyerlein et al 2011).…”
Section: Discussionmentioning
confidence: 99%